1995
DOI: 10.1016/s0006-3495(95)80396-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for localized cell heating induced by infrared optical tweezers

Abstract: The confinement of liposomes and Chinese hamster ovary (CHO) cells by infrared (IR) optical tweezers is shown to result in sample heating and temperature increases by several degrees centigrade, as measured by a noninvasive, spatially resolved fluorescence detection technique. For micron-sized spherical liposome vesicles having bilayer membranes composed of the phospholipid 1,2-diacyl-pentadecanoyl-glycero-phosphocholine (15-OPC), a temperature rise of approximately 1.45 +/- 0.15 degrees C/100 mW is observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
218
4
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(239 citation statements)
references
References 28 publications
12
218
4
1
Order By: Relevance
“…This magnitude of heating is in agreement with experimentally observed laser-induced heating of vesicles by infrared optical tweezers (Liu et al, 1995), of DNA in an infrared optical trap (Braun and Libchaber, 2002), of micron-sized silica and polystyrene beads in a optical traps (Peterman et al, 2003), and temperature sensitive dyes in buffer suspension in an infrared dual-beam laser trap (Ebert et al, 2007). We find that for spot sizes with w s = 1-2 m, we have d hm = 32.7 m, which is comparable to the diameter of a neuronal growth cone.…”
Section: D Temperature Field For a Stationary Laser Spotsupporting
confidence: 91%
“…This magnitude of heating is in agreement with experimentally observed laser-induced heating of vesicles by infrared optical tweezers (Liu et al, 1995), of DNA in an infrared optical trap (Braun and Libchaber, 2002), of micron-sized silica and polystyrene beads in a optical traps (Peterman et al, 2003), and temperature sensitive dyes in buffer suspension in an infrared dual-beam laser trap (Ebert et al, 2007). We find that for spot sizes with w s = 1-2 m, we have d hm = 32.7 m, which is comparable to the diameter of a neuronal growth cone.…”
Section: D Temperature Field For a Stationary Laser Spotsupporting
confidence: 91%
“…20 Liu et al have reported that the temperature rise of a lipid directly irradiated by the IR laser with 100 mW and a focused spot size of 0.8 m in water is about 1.5°C. 21 In our system, the spot size is larger Í‘ÏŸ1 m͒ for 100 mW and most of the laser illuminates the cantilever, which is separated from the surface about 1 m. Therefore it is expected that the IR laser does not rise sample temperature so much. In fact, obvious structural alterations of proteins were not observed when an IR laser was used.…”
Section: Imaging Of Biological Moleculesmentioning
confidence: 91%
“…The temperature increases as much as 10, 11.5, and 14.5°C / W, respectively. 139,140 Local heating is a serious issue in trapping cells as heat adversely affects enzyme activity and other sensitive cellular functions; also, steep thermal gradient might cause a convection current that disrupts laminar flow in the microfluidic channel. Therefore, there is much room to improve and potentially in combination with other physical and chemical trapping techniques.…”
Section: Laser/optical Trappingmentioning
confidence: 99%